Solving A Fuel Distribution Problem Using Genetic Algorithm: A Traveling Salesman Problem Approach - Abd Rahman, Rosshairy; Mokhtar, Nurul Ezatty; Bahrom, Ummu Latifah (UUM Press, 2017)
Petrol or fuel is the product that people use daily and have a high demand. Therefore, the delivery of petrol from origin to each petrol station is done daily. This distribution process concerns the management as they have to minimize the cost while maximizing the profit. Hence, this paper aims to develop a model that is able to determine the shortest path for delivery this petrol in one company in Selangor. The problem is solved using Traveling Salesman Problem (TSP) approach, where the data were collected using Google Maps application. The shortest distance was attained using Genetic Algorithm (GA) technique. The solution obtained from GA was then compared with Hill Climbing technique. The results shows that GA produces better solution and could cut the distance up to 23 km. The finding of this research would help the company to reduce the cost of distributing refined fuel around Selangor.